Smoking and the Pathophysiology of Peripheral Artery Disease - Wang, Weiming; Zhao, Tingting; Geng, Kang; Yuan, Gang; Chen, Yue; Xu, Youhua (Frontiers in Cardiovascular Medicine, 2021)
Smoking is one of the most important preventable factors causing peripheral artery disease (PAD). The purpose of this review is to comprehensively analyze and summarize the pathogenesis and clinical characteristics of smoking in PAD based on existing clinical, in vivo, and in vitro studies. Extensive searches and literature reviews have shown that a large amount of data exists on the pathological process underlying the effects of cigarette smoke and its components on PAD through various mechanisms. Cigarette smoke extracts (CSE) induce endothelial cell dysfunction, smooth muscle cell remodeling and macrophage phenotypic transformation through multiple molecular mechanisms. These pathological changes are the molecular basis for the occurrence and development of peripheral vascular diseases. With few discussions on the topic, we will summarize recent insights into the effect of smoking on regulating PAD through multiple pathways and its possible pathogenic mechanism.